An evaluation of high-resolution gridded precipitation products over Bhutan (1998-2012) - Khandu; Awange, Joseph; Forootan, E. (John Wiley and Sons Ltd, 2015)
Several global and regional high-resolution precipitation products have been released over the past decade by combining precipitation estimates from various sources including satellite-based measurements and gauge-based observations. With relatively few validation studies over the Eastern Himalayan region, this study examined seasonal and interannual skills of four gridded precipitation products including the regional gauge-based APHRODITE (Asian Precipitation-Highly Resolved Observational Data Integration Towards Evaluation of Water Resources) and three near-global satellite-based products: Tropical Rainfall Measuring Mission (TRMM), Climate Prediction Centre (CPC) MORPHing (CMORPH), and Climate Hazards Group InfraRed Precipitation (CHIRP) using in-situ rain gauge data from Bhutan for the period 1998–2012. Principal component analysis (PCA) was used to assess the dominant rainfall patterns over Bhutan. An attempt has also been made to correct precipitation biases in the satellite-only products using a gamma (γ)-based distribution approach. Results indicated that APHRODITE and satellite-based precipitation products were able to adequately capture the spatio-temporal patterns of rainfall variability over Bhutan. Extreme precipitation events and extreme drought periods were well captured with very good correlations (>0.5). APHRODITE and TRMM 3B43v7 were remarkably similar, whereas satellite-only products (CMORPH and CHIRP) highly underestimated (20–60% or 200–450 mm month−1) monsoon rainfall over Bhutan. While TRMM 3B43v7 still underestimated monsoon rainfall (by ∼25%), it has significantly improved the seasonal bias (by 20–40%) from its previous version (TRMM 3B43v6). CHIRP performed relatively better in the high rainfall regions but indicated very low correlations over mountainous regions and during the pre- and post-monsoon season. The bias correction approach indicated best results for TRMM 3B43v6 (up to 33%) in the Southern Foothills, whereas satellite-only products improved only moderately (5–20%).